Fatal Flaw of AI Implementation - W., Jeanne Ross (MIT Sloan Management Review, 2018)
Many managers are excited about smart machines but are struggling to apply machines' limited intelligence. Indeed, computers can process data just fine, but to generate competitive advantage from machine learning applications, organizations must upgrade their employees' skills. Companies will also need to redesign employee accountabilities to empower and motivate them to deploy smart machines when doing so will enhance outcomes.